An Open-Access Data Platform: Global Nutrition and Health Atlas (GNHA). Issue 4 (11th March 2022) - Zhou, Bingjie; Liang, Shiwei; Monahan, Kyle M; El-Abbadi, Naglaa; Cruz, Melissa S; Chen, Yutong; DeVane, Annie; Reedy, Julia; Zhang, Jianyi; Semenova, Iaroslava; Montoliu, Ivan; Mozaffarian, Dariush; et al.
ABSTRACT: The rapid development of nutrition science is embracing digital transformation to generate large amounts of data. Precision nutrition and "Big Data" place increasing demand for data repositories and visualization, which enhances the digital transformation. We defined the need for an integrated nutrition data platform as a web-based platform that can collect, store, track, analyze, monitor, and visually display key metrics in nutrition and health while allowing users to interact with visuals and download data provided in the platform. Interactive dashboards create new opportunities for scholars and practitioners to generate and test hypotheses. We present the development and implementation of the Global Nutrition and Health Atlas (GNHA; https://sites.tufts.edu/gnha/ ), an open-access online platform covering nutrition and health data with 26 themes and 500+ indicators from 190+ countries up to 30 y. We view GNHA as an interactive tool aiming to share information and perspectives and foster collaborations and innovations.